STUDENT’S SPEAKING SKILL OF FOREIGN SPEAKER IN BIPA LEARNING - Noviani Radna Sari; Syafriyadin Syafriyadin (Jurnal Kata, 2024)
Although BIPA students possess the speaking skill to communicate in Indonesian, the noticeable influence of foreign languages is still evident. Therefore, this study aims to analyze and describe student’s speaking skills as foreign speakers in BIPA learning. In order to accomplish this goal, a qualitative research method was used to gather data from a BIPA student who was still struggling to speak Indonesian fluently. The results show that he frequently ceased to speak Indonesian, used the sentences in accordance with their context, and extended a greeting to his teacher during an online Zoom meeting. Additionally, he addressed questions presented by the teacher. He continued to lack understanding of Indonesian grammar and structure, as well as vocabulary mastery. The video suggests that the BIPA student was reading the notebook while practicing counting. It lacked authenticity. As a result, the Indonesian language became the native tongue. Based on this research, the teacher needs to request that the BIPA student engage in additional practice.